The Involvement of UiTM Rembau student towards e-sport / Wan Haziq Iqbal Iqbal Wan Kamarulzaman - Wan Kamarulzaman, Wan Haziq Iqbal Iqbal (2018)
Electronic sport or E-sport, are competitive events that involve the use computers and online video games to compare the skills and intelligence of the people of people who play. It been increasing in popularity over the coming years by having it own audience following that similar as traditional sport such as football. Therefore, this concept paper, researcher provide the rises of E-sport in Malaysia. The researcher will explain how E-sport in Malaysia develop as sport in Malaysia. There are a lot of competition that happened and will held in Malaysia. But if teenagers attend to play video games, that will affect their lifestyle such as behavior, health academic. Many students mostly university students involve in E-sport during leisure time. They are spending time on watching and playing Esport. This research was proposed to know the involvement students in UiTM Rembau toward E-sport.